2014
DOI: 10.1056/nejmoa1401106
|View full text |Cite
|
Sign up to set email alerts
|

Clonidine in Patients Undergoing Noncardiac Surgery

Abstract: Administration of low-dose clonidine in patients undergoing noncardiac surgery did not reduce the rate of the composite outcome of death or nonfatal myocardial infarction; it did, however, increase the risk of clinically important hypotension and nonfatal cardiac arrest. (Funded by the Canadian Institutes of Health Research and others; POISE-2 ClinicalTrials.gov number, NCT01082874.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
148
3
12

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 309 publications
(166 citation statements)
references
References 22 publications
3
148
3
12
Order By: Relevance
“…2 Although agents such as clonidine 53 and beta blockers have shown promise in reducing perioperative cardiac events, the large randomized-controlled POISE studies showed an increase in mortality and stroke with perioperative beta blocker therapy 4 and increases in clinically important hypotension and non-fatal cardiac arrest with clonidine. 6 Therefore, the search continues for effective agents that can reduce perioperative myocardial events in high-risk patients without increasing such adverse events as hypotension and bradycardia and therefore all-cause mortality. Although such perioperative events as intubation, extubation, surgery, and pain can contribute to increasing myocardial demand, 3 our review focused only on the brief hemodynamic response following intubation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Although agents such as clonidine 53 and beta blockers have shown promise in reducing perioperative cardiac events, the large randomized-controlled POISE studies showed an increase in mortality and stroke with perioperative beta blocker therapy 4 and increases in clinically important hypotension and non-fatal cardiac arrest with clonidine. 6 Therefore, the search continues for effective agents that can reduce perioperative myocardial events in high-risk patients without increasing such adverse events as hypotension and bradycardia and therefore all-cause mortality. Although such perioperative events as intubation, extubation, surgery, and pain can contribute to increasing myocardial demand, 3 our review focused only on the brief hemodynamic response following intubation.…”
Section: Discussionmentioning
confidence: 99%
“…Clonidine has also shown initial promise, 5 although results of the recent POISE 2 study showed no reduction in cardiac events or mortality and an increase in clinically significant hypotension and non-fatal cardiac arrest. 6 Therefore, the search for alternative agents that do not produce such adverse effects is a clinically important issue for high-risk patients undergoing surgery.…”
Section: Résumémentioning
confidence: 99%
“…However, the sample was extremely significant. [27] Similarly, there are still controversies with respect to the adequate dose in intrathecal use of clonidine, with various studies recommending doses of 15 to 450 µg. The majority suggest adjusting the dose by factors such as age, time in surgery, presence of co-morbid conditions, and the dose of local anaesthetics and opioids used.…”
Section: Discussionmentioning
confidence: 99%
“…This may trigger plaque rupture and acute coro nary syndromes (ACS) perioperatively [33]. Thus, in an attempt to prevent MINS or major adverse cardiac events (MACE) in the perioperative setting, various agents including βblockers, α2adrenergic antagonists, statins and aspirin (acetylsalicylic acid, ASA) have been trialed to reduce the sympathetic response [8,34], stabilise coronary plaque [35] or to inhibit platelet function [8,36].…”
Section: Evidence-based Perioperative Pharmacologymentioning
confidence: 99%